Population structure of managed Brazil nut trees (Bertholletia excelsa) in the Caxiuanã National Forest, Pará - Sousa, Diego Guimarães de; Almeida, Samuel Soares de; Amaral, Dário Dantas do (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
This paper presents assessment of the abundance and population structure of the Brazil nut, Bertholletia excelsa, in primary and secondary forests in the Caxiuanã National Forest reserve in the state of Pará, Brazil. A total of 121 individuals saplings, (DBH < 10 cm), juveniles (10 cm ≤ DBH < 50 cm) and adults (≥ 50 cm DBH), were inventoried. Notable results included (1) a very high density of juveniles and adults with some 25 + 14.3 individuals ha-1; (2) the distribution of sampled individuals was regular; (3) the population is assumed to be in dynamic equilibrium with an inverted J-shaped distribution; (4) 54.5% of the total inventoried Brazil nuts are saplings or juveniles, which were very abundant in areas of secondary forests, indicating that the species can benefit from human disturbance; (5) the use of fire for the cleaning of the understory to facilitate the collection of Brazil nut fruits, as well as the establishment of the ‘slash-and-burn’ agriculture can facilitate self-regeneration while also contributing to the frequent bifurcation observed in Brazil nut tree stems in the Caxiuanã National Forest.
Keywords: Population ecology; Demography; Extractivism